MANAJEMEN PELAKSANAAN PEMANTAUAN PERTUMBUHAN TERHADAP PARTISIPASI KEHADIRAN DAN STATUS GIZI BALITA - Sitanggang, Berlin (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2020)
ABSTRACT   Growth monitoring can be done at the level of individual or group through the weighing weight toddlers regularly each month. Monitoring the growth of information in the form of quantity growth disorder problems in toddlers from time to time as well as being the reference in program planning and policy improvements in the nutritional levels of clinics and posyandu (Health RI, 2008). The purpose of the research was to know relationship management implementation monitoring of growth towards the attainment of the presence of the posyandu and nutritional status of infants in the region of clinics Cape Banyan Kec. Tanjung Beringin. The study was observational research with qualitative approach. The research design used was the study cut latitude (cross sectional). The subject was the health officers and 77 samples of toddlers are determined based on the terms of inclusion criteria. Data collection is done with the form questionnaire and Anthropometry measurements i.e. weight. Data analysis using chi-square test. The results showed there is a meaningful relationship between the management of the implementation of the monitoring of growth against the participation presence (p = 0.000), there is a meaningful relationship between the management of the implementation of the monitoring of growth towards nutritional status (toddler p = 0.025) Conclusion the research indicates that there is a correlation between the management of the implementation of the monitoring of growth against the presence and participation of the nutritional status of children in the region of the Clinics Tanjung Beringin.   Keywords: Management monitoring growth, nutritional status of children, presence of Participation.